Convergence Theorems for Two Simultaneous Quasinonexpansive Mappings in Banach Spaces - Satit Saejung; Pongsakorn Yotkaew (Journal of Mathematics)
We discuss the approximation method of finding a common fixed point of two certain mappings defined on a Banach space. This paper deals with three modes of convergence, namely, weak, strong, and △-convergences in the presence of the uniform convexity of the norm. It is worth mentioning that the △-convergence which is closely connected with the weak convergence is discussed without assuming the Opial’s condition. Our results not only generalize the results recently announced by Garodia et al. but also rectify a gap in their paper. Finally, some concrete numerical examples are shown that our results are genuine generalizations of a number of results in the literature.